(Co)polymerization of ethylene via nonmetallocene catalysts with diphenyl phosphoroso schiff‐base ligand. Issue 28 (31st March 2015) - Wang, Jing; Zhang, Xinli; Zhou, Lu; Zhou, Yang; Huang, Qigu; Yang, Wantai
ABSTRACT A series of novel nonmetallocene catalysts [N, O, P] with diphenyl phosphoroso ligands were synthesized by the treatment of phthaldialdehyde, substituted phenols, chlorodiphenyl phosphine with metal halides of TiCl4 and ZrCl4. The catalyst microstructure was characterized by 1H NMR and EA. After activated by methylaluminoxane (MAO), these [N, O, P] catalysts were utilized to catalyze the polymerization of ethylene and the copolymerization of ethylene with 1‐octene. The results indicated that the obtained catalysts were highly efficient for ethylene polymerization and ethylene/1‐octene copolymerization. Structures and properties of the obtained polymers were measured by WAXD, DSC, GPC, and 13C NMR. The results indicated that polyethylene catalyzed by Cat.3 possessed the highest weight‐average molecular weight of 1.025 × 106 g/mol and the highest melting point of 136.3°C. The copolymer of ethylene/1‐octene catalyzed by Cat.1 exhibited the highest 1‐octene incorporation content of 0.63 mol %. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42225.